Methodology to estimate fuel`s exergy in SI engines using Otto cycles principles limited by the knock. (LACCEI, 2024)
A novel methodology is presented to estimate the exergy of liquid and gaseous fuels for spark ignition (SI) engines, based on the thermodynamics laws and two scientific methodologies, one for fuel´s methane number (MN) measurements, and the other for gaseous fuel´s energy quality quantification. Two engines were used 1) A CFR engine to measure fuel's critical CR and MN, fuels with MNs ranging from 37 to 140 were used, two biogases, methane, propane, and blends of biogas with methane/propane and hydrogen. 2) A hybrid diesel engine with a high compression ratio (CR) converted to SI using custom pistons for high turbulence intensity designed by CFD simulations, for biogas SI (BSI) combustion, the BSI engine combines diesel engines characteristics (high airflow inlet, and high combustion pressures) with SI engines characteristics (premixed combustion using SI for combustion phasing at the knocking threshold (KT)). The BSI engine was used to measure the fuel´s maximum electrical energy generation and thermal efficiency at the KT. Correlations between MN and research octane number (RON) were used to develop the methodology. Fuel´s exergy efficiency is estimated with fuel´s γ, hydrogen/carbon (H/C) ratio, and limited by fuel´s MN/RON. Fuel´s exergy is correlated with fuel´s entropy, adiabatic flame temperature (Tad), and fuel´s exergy efficiency for Otto cycles limited by the knock.